Mixed-matrix membranes with metal-organic framework-decorated CNT fillers for efficient CO2 separation - Lin, R.; Ge, L.; Liu, Shaomin; Rudolph, V.; Zhu, Z. (American Chemical Society, 2015)
Carbon nanotube (CNT) mixed-matrix membranes (MMMs) show great potential to achieve superior gas permeance because of the unique structure of CNTs. However, the challenges of CNT dispersion in polymer matrix and elimination of interfacial defects are still hindering MMMs to be prepared for high gas selectivity. A novel CNT/metal–organic framework (MOF) composite derived from the growth of NH2-MIL-101(Al) on the surface of CNTs have been synthesized and applied to fabricate polyimide-based MMMs. Extra amino groups and active sites were introduced to external surface of CNTs after MOF decoration. The good adhesion between the synthesized CNT-MIL fillers and polymer phase was observed, even at a high filler loadings up to 15%. Consequently, MMMs containing the synthesized MOF/CNT composite exhibit not only a large CO2 permeability but also a high CO2/CH4 selectivity; the combined performance of permeability and selectivity is even above the Robeson upper bound. The strategy of growing MOFs on CNTs can be further utilized to develop a more effective approach to further improve MMM performance through the decoration of MOFs on existing fillers that have high selectivity to specific gas.